Optimization Of The Ake Gaale Regional Drinking Water Company On Sea Water Pollution And Sanitation In Clean Water Management In Ternate City - Aja, Nursia; Tri Kartono, Drajat; Hi.Soleman, Saiful (Publisher Cv. Inara, 2022)
Ternate has abundant groundwater/spring water reserves. The potential for groundwater reserves is not managed properly and correctly, so that in 2014 the City of Ternate experienced a very serious water shortage (crisis), this was due to a decrease in water discharge from one of the Biggest Springs on Ternate Island, namely the Ake Gaale spring, which has decreased its discharge by 25%. This condition is exacerbated by the occurrence of sea water intrusion which has resulted in almost all beaches of Ternate Island experiencing an increase in salinity (salobar) as a result of excessive groundwater extraction. optimization of local drinking water company (PDAM) Ake Gaale against sea water pollution and sanitation in clean water management. As far as this research is concerned, it is hoped that the prevalence of sea water pollution and sanitation is one of the factors that can increase morbidity and mortality compared to clean water sanitation for sea water pollution, as well as having a long-term impact on the growth and development of prevention of sea water pollution and sanitation in management clean water in Ternate City. Sustainable Development Goals targeting the fulfillment of the needs for 100% of citizens (by name by address) in 2030 with the no one left behind spark. So efforts to achieve the development target are not only by building access or facilities from each pillar of its development, but an effort is needed to maintain the sustainability of built access or standardized facilities that are owned by residents. The results of the identification of proper drinking water sources, where 65 people (42.1%) have met the category of safe and proper drinking water in accordance with health standards.